CpG Methylation in TGFβ1 and IL-6 Genes as Surrogate Biomarkers for Diagnosis of IBD in Children. Issue 10 (14th May 2020) - Samarani, Suzanne; Dupont-Lucas, Claire; Marcil, Valerie; Mack, David; Israel, David; Deslandres, Colette; Jantchou, Prevost; Ahmad, Ali; Amre, Devendra
Abstract: Background: Diagnostic markers for distinguishing between Crohn disease (CD) and ulcerative colitis (UC) remain elusive. We studied whether methylation marks across the promoters of the transforming growth factor beta 1 ( TGFβ1 ) and interleukin-6 genes have diagnostic utility. Methods: A case-control study was carried out. Cases were treatment-naïve, diagnosed before age 20, and recruited from 3 pediatric gastroenterology clinics across Canada. Control patients did not have inflammatory bowel disease and were recruited from orthopedic clinics within the same hospitals as the gastroenterology clinics. Patient DNA from peripheral blood was processed to identify methylation sites (CpG) across the promoter regions of the TGFβ1 and interleukin-6 genes. After initial nonparametric univariate analyses, multivariate logistic regression models were fit. Models with the best fit (Akaike information criteria) and strongest discriminatory capabilities (area under the curve [AUC]) were identified, and P values were adjusted for multiple comparisons using the false discovery rate method. Results: A total of 67 CD, 31 UC, and 43 control patients were included. The age distribution of the 3 groups was similar. Most CD patients had ileocolonic disease (44.8%) and inflammatory disease (88.1%). Most UC patients had extensive (71%) and moderate disease (51.6%). Logistic regression analysis revealed the following: 14 TGFβ1 CpG sites discriminated between CD and control patients (AUC = 0.94), 9 TGFβ1 CpG sites discriminated between UC and control patients (AUC = 0.99), 3 TGFβ1 CpG sites discriminated between CD and UC (AUC = 0.81), and 6 TGFβ1 CpG sites distinguished colonic CD from UC (AUC = 0.91). Conclusions: We found that CpG methylation in the promoter of the TGFβ1 gene has high discriminative power for identifying CD and UC and could serve as an important diagnostic marker. Abstract : Diagnostic biomarkers for inflammatory bowel disease in children remain elusive. Here we report that methylation marks in the transforming growth factor beta 1 and interleukin-6 genes have strong capabilities to serve as potential diagnostic markers for CD and UC.